A Review of Credit Guarantee Schemes in the Middle East and North Africa Region - Saadani, Youssef; Arvai, Zsofia; Rocha, Roberto (2012)
Many countries in the MENA region have established partial credit guarantee schemes to facilitate SME access to finance. These schemes can play an important role, especially in a period where MENA governments are making efforts to improve the effectiveness of credit registries and bureaus and strengthen creditor rights. This paper reviews the design of partial credit guarantee schemes in MENA, and assesses their preliminary outcomes. The paper is based on a survey conducted in 10 MENA countries in early 2010. The authors find that the average size of guarantee schemes in MENA (measured by the total value of outstanding guarantees) is in line with the international average, although there are wide differences across countries, and some schemes seem too small to make any significant impact. Most importantly, the number of guarantees looks generally small while their average value looks large. This suggests that guarantee schemes are not yet reaching the smaller firms. Guarantee schemes in MENA look financially sound and most schemes have room to grow. However, this growth should be accompanied by an improvement of some key design and management features, as well as the introduction of systematic impact evaluation reviews.